The adolescent motor performance development of elite female soccer players: A study of prognostic relevance for future success in adulthood using multilevel modelling. Issue 11 (17th June 2020) - Leyhr, Daniel; Raabe, Johannes; Schultz, Florian; Kelava, Augustin; Höner, Oliver
ABSTRACT: Considering the scarce empirical evidence regarding talent predictors in female youth soccer, the present study aimed to investigate the long-term prognostic validity of elite female soccer players' adolescent motor performance for future success in adulthood. Additionally, the three-year development of highly talented girls' motor performance and the predictive value of this motor development for reaching a professional adult performance level (APL) was analysed. Overall, N = 737 female players participated in nationwide motor diagnostics (sprinting, agility, dribbling, ball control, shooting) within the German Soccer Association's talent identification and development programme at least twice between the age groups Under-12 (U12) and U15. Based on their APL at least four years later, participants were assigned to a professional (first German division, 6.2%) or non-professional group (lower divisions, 93.8%). Multilevel regression analyses revealed a general prognostic relevance for the investigated parameters with respect to players' APL. In addition, there was a non-linear improvement in participants' motor performance across all variables from U12 to U15. However, non-significant interactions between APL and these improvements indicate motor performance development itself cannot adequately predict players' future success in adulthood. Findings provide insightful information that can help coaches foster optimal support for young female soccer players' development.